1991
DOI: 10.1007/bf02074075
|View full text |Cite
|
Sign up to set email alerts
|

Homeless mentally disordered offenders and violent crimes: Preliminary research findings.

Abstract: This study examines the prevalence of homelessness in a cross-sectional sample of 150 patients retained in a maximum-security hospital for mentally disordered offenders in New York City. The homeless mentally ill comprise only 2% of the city's mentally ill population, yet they account for 50% of the admissions to this forensic facility from the community. Compared to population base rate estimates, forensic patients are homeless at 25 times the rate found in the rest of the city's mentally disordered populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…(Polczynski, 2007). However, in an earlier study, Martell (1991) found the mentally ill homeless represented 50% of all admissions to a New York City maximum security hospital. This study suggested a higher base rate of violent criminal behavior in this population and the existence of a subgroup that might pose a threat to public safety secondary to violent behavior.…”
Section: Individual Outcomesmentioning
confidence: 96%
See 1 more Smart Citation
“…(Polczynski, 2007). However, in an earlier study, Martell (1991) found the mentally ill homeless represented 50% of all admissions to a New York City maximum security hospital. This study suggested a higher base rate of violent criminal behavior in this population and the existence of a subgroup that might pose a threat to public safety secondary to violent behavior.…”
Section: Individual Outcomesmentioning
confidence: 96%
“…As found, homeless inmates are more likely to have been charged with violent offenses, thus raising questions about public safety. The previously noted factors of untreated mental illness, substance abuse, disaffiliation, and lack of social support may increase issues of recidivism and subsequently public safety (Martell, 1991;Polczynski, 2007).…”
Section: Social Outcomesmentioning
confidence: 98%
“…The fi rst is that homelessness itself may be crimogenic, refl ecting efforts of homeless individuals to survive with limited resources (Fischer, 1988(Fischer, , 1992Snow et al, 1989;McCarthy and Hagen, 1991). The second is that poor health status, especially substance abuse and/or mental illness, common among homeless individuals, increases their risk of criminal justice system involvement (Benda, 1993;Desai et al, 2000;Fischer, 1988Fischer, , 1992Kushel et al, 2005;Lindelius and Salum, 1976;Snow et al, 1989;Gelberg et al, 1988;Martell, 1991;Martell et al, 1995). Thirdly, some socio-demographic characteristics (being male, single, young, poor, of minority ethnicity or being poorly educated) have been found to be associated with both homelessness and risk of criminal justice system involvement in some but not all studies (Blakely, 1992;Solomon and Draine, 1995;Michaels et al, 1992;Martell, 1991;Martell et al, 1995;DeLisi, 2000;Richman et al, 1992;Solomon et al, 1992;Vitelli, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The second is that poor health status, especially substance abuse and/or mental illness, common among homeless individuals, increases their risk of criminal justice system involvement (Benda, 1993;Desai et al, 2000;Fischer, 1988Fischer, , 1992Kushel et al, 2005;Lindelius and Salum, 1976;Snow et al, 1989;Gelberg et al, 1988;Martell, 1991;Martell et al, 1995). Thirdly, some socio-demographic characteristics (being male, single, young, poor, of minority ethnicity or being poorly educated) have been found to be associated with both homelessness and risk of criminal justice system involvement in some but not all studies (Blakely, 1992;Solomon and Draine, 1995;Michaels et al, 1992;Martell, 1991;Martell et al, 1995;DeLisi, 2000;Richman et al, 1992;Solomon et al, 1992;Vitelli, 1993). Finally, it has been suggested that the association between homelessness and incarceration may be bi-directional in that incarceration increases the risk of homelessness by reducing community and family ties as well as opportunities for employment and public housing (Kushel, 2005;Travis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A body of research has also demonstrated that individuals with lower IQ levels are more likely to commit more severe (and violent) offences (Crocker & Hodgins, 1997;Hayes & McIIwain, 1988;Martell, 1991). Additionally, evidence exists which demonstrates that criminal offenders have lower IQ's than non-offenders (Feldman, 1993;Herrnstein & Murray, 1994;Wilson & Herrnstein, 1985).…”
Section: Intelligence and Crimementioning
confidence: 99%